2013
DOI: 10.1007/s00228-013-1578-5
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin abuse among opiate addicted patients

Abstract: Our data suggest that pregabalin is liable to be abused among individuals with opiate dependency syndrome Thus, vigilance and caution are called for when patients with a past or current opiate dependency are exposed to treatment with pregabalin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 21 publications
5
69
0
9
Order By: Relevance
“…Pregabalin was detected in 12.1 % (n = 15) of urine samples from opiate-addicted subjects attending a German addiction clinic. None of these patients were suffering from any of the indications for pregabalin prescribing, with most having confirmed that they had acquired pregabalin illicitly whilst being well aware that the molecule was not included in the standard drug monitoring system [2]. Similarly, Baird et al [33] carried out a questionnaire-based survey in six Scottish substance misuse clinics; 22 % (29/129) of respondents admitted to abusing gabapentinoids, with 38 % (11/29) of these clients abusing these molecules to potentiate the 'high' they obtained from methadone.…”
Section: Addiction Clinics' Surveys; Results From Online Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Pregabalin was detected in 12.1 % (n = 15) of urine samples from opiate-addicted subjects attending a German addiction clinic. None of these patients were suffering from any of the indications for pregabalin prescribing, with most having confirmed that they had acquired pregabalin illicitly whilst being well aware that the molecule was not included in the standard drug monitoring system [2]. Similarly, Baird et al [33] carried out a questionnaire-based survey in six Scottish substance misuse clinics; 22 % (29/129) of respondents admitted to abusing gabapentinoids, with 38 % (11/29) of these clients abusing these molecules to potentiate the 'high' they obtained from methadone.…”
Section: Addiction Clinics' Surveys; Results From Online Data Analysismentioning
confidence: 99%
“…This may be considered an observation that is in apparent contrast with gabapentinoids, similar to benzodiazepines, being GABA analogues only [26]. With a relatively short half-life of about 6 h, gabapentinoids are mostly ([98 %) excreted unchanged in the urine [15], with a urine specimen being positive for pregabalin for up to 5-6 days after intake in subjects with normal renal function [2].…”
Section: Methods/literature Search Strategymentioning
confidence: 98%
See 1 more Smart Citation
“…In a study, 12.1% of 124 patients with opiate dependence were found to be pregabalin positive in urine test, and none of these patients reported using pregabalin because of medical indications (22). The common features of the cases in the literature are: pregabalin is used at much higher doses than treatment doses; even though there have been uses via intravenous or rectal routes, most of the cases take orally; the effect occurs within 10 minutes to 2 hours; tolerance and withdrawal develops very rapidly (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…35,42 Opioid treatment programmes have reported approximately 10% of patients test positive for pregabalin, the majority of whom were not prescribed this medication. 43,44 Co-misuse of gabapentinoids and opioids is particularly concerning because high-dose pregabalin may exaggerate the respiratory depression seen with opioid use. 35 Seventy-nine percent of deaths attributed to gabapentinoids also involved opioids.…”
Section: Patterns Of Misusementioning
confidence: 99%